Menjelajahi Keseimbangan antara Tuntutan Akademik dan Komitmen: Potret Flourishing Mahasiswa-atlet di Pendidikan Tinggi - Nadia Aulia Nadhirah; Irfan Oktavianus; Adiska Rani Ditya Candra; Risma Nursyani; M Solehuddin; Sudaryat Nurdin Akhmad; Syamsu Yusuf; Ilfiandra Ilfiandra (Jurnal Sporta Saintika, 2026)
This study explores the flourishing experiences of student-athletes who navigate the dual challenges of academic and athletic commitments in Indonesian higher education. Within a context where student-athletes often face conflicts between training demands and educational expectations, the research aims to understand how they construct well-being and balance through the lens of positive psychology. Using a qualitative approach with Reflexive Thematic Analysis (RTA), eight participants from diverse sport disciplines were interviewed in depth. The PERMA (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment) served as a sensitizing concept to guide analysis while remaining open to emergent themes. Findings reveal that flourishing develops through the adaptive integration of positive emotions, deep engagement, supportive social relationships, purposeful dual-role identity, and balanced achievements. Participants experienced a process of self-regulation, resilience, and meaning-making as they coped with physical fatigue, academic stress, and time management challenges. These processes reflected both hedonic and eudaimonic dimensions of well-being. The study underscores that flourishing is not a static state but a reflective and ecological process shaped by social support, institutional context, and personal strengths. The findings highlight the need for strength-based counseling programs and flexible institutional policies to sustain student-athletes’ holistic well-being and long-term academic–athletic harmony.